Rhodium‐Catalyzed Intramolecular C−H Silylation by Silacyclobutanes. (13th April 2016) - Zhang, Qing‐Wei; An, Kun; Liu, Li‐Chuan; Guo, Shuangxi; Jiang, Chenran; Guo, Huifang; He, Wei
Abstract: Silacyclobutane was discovered to be an efficient C−H bond silylation reagent. Under the catalysis of Rh I /TMS‐segphos, silacyclobutane undergoes sequential C−Si/C−H bond activations, affording a series of π‐conjugated siloles in high yields and regioselectivities. The catalytic cycle was proposed to involve a rarely documented endocyclic β‐hydride elimination of five‐membered metallacycles, which after reductive elimination gave rise to a Si−Rh I species that is capable of C−H activation.